A roadmap for exploring the thematic content of ecology journals. Issue 8 (1st August 2019) - Knott, Jonathan; LaRue, Elizabeth; Ward, Samuel; McCallen, Emily; Ordonez, Kimberly; Wagner, Franklin; Jo, Insu; Elliott, Jessica; Fei, Songlin
Abstract: Ecologists—especially those new to the field—are tasked with finding relevant literature matching their research interests and deciding upon a suitable venue for the publication of their work. To provide a roadmap for early career researchers to identify journals aligned with their interests, we analyzed major research themes found across the top 30 ecology journals and three high‐impact multi‐disciplinary journals ( Nature, PNAS, and Science ), utilizing an automated content analysis (ACA) of 84, 841 article abstracts, titles, and author keywords published over the last four decades. Journals clustered into 10 distinct groups based on 46 research themes identified by ACA. We examined the frequency of ecological themes in each of these journal groups to identify the journals most associated with each theme. We found three themes ( anthropogenic impacts, disease, and traits ) that occurred at a high frequency in the high‐impact multi‐disciplinary journal group containing Nature, PNAS, and Science . Themes that increased in frequency over the last four decades, such as climate change, traits, anthropogenic, and cellular biology, were found more often in journals with higher impact factors, indicating that emerging research themes in ecology will likely become of interest to a broader readership over time. Our study provides a thematic review as a potential roadmap for junior ecologists to browse and publish journal articles.